Assessing and Evaluating the General Legal Characteristics of War Crimes: A Basic Necessity or a Confused Platform - Hennadii Yevhenovych Bershov; Oksana Anatolyevna Hrytenko; Vadym Heorhiiovych Khashev; Mykhailo Ihorevych Fialka (Ius Humani. Jornal do direito, 2022)
The general legal characteristics of war crimes allow to comprehensively study the indicated acts, to understand their essence, which in turn should facilitate and improve the quality of criminal qualification of criminal offenses against performing the established procedure of active service. The need to form general legal characteristics of war crimes is due to the fact that the sphere of public relations related to active service is intersectoral, since it is simultaneously regulated by the norms of various branches of law. The authors have found out the main features of war crimes and have carried out their characteristics by determining the specific features of their regulation both by criminal and other branches of law. The authors have provided an analytical basis for this in order to evaluate the provisions of regulatory legal acts regulating the procedure of active service and determine the main features of war crimes. The findings of the research was that war crimes infringe the statutory order of performing active service, and the subjects of such illegal acts are military personnel, persons liable to military duty and personnel with reserve obligations during the battle assembly. The general legal characteristics of war crimes is formed taking into account criminal and legal features of the specified criminal offenses and defines specific features of active service; the established procedure for performing active service; military personnel, persons liable to military duty and personnel with reserve obligations during the battle assembly as subjects of crime.